Research on Epidermis and Epidermal Derivates of Bitter Mustard (Brassica juncea L.) and Petsai Mustard (Brassica pekinensia L.) Leaves in Batang Regency - Faisal, Muhammad Faisal; Yoan Dea Irawati; Zuchrotus Salamah (Universitas Ahmad Dahlan, 2023)
This research is an exploratory study conducted in Batang Regency. The research samples, namely bitter mustard (Brassica juncea L.) and petsai (Brassica pekinensia L.) leaves, were collected in December 2022. The selection of research samples is based on the level of production and availability. The data analysis method used in the research is descriptive quantitative analysis. The results showed that bitter mustard (Brassica juncea L.) and petsai mustard (Brassica pekinensia L.) have the same epidermal characteristics, namely irregularly shaped epidermal cells with notched cell wall edges and elongated polygonal cells with flat cell wall edges. The epidermal derivatives found are stomata and trichomes. The stomata of the study sample have anisocytic type, closed slit condition, but have different sizes (length and width), index and density. Trichomes have a simple needle-like hair type on the edge of the leaf, but have different sizes (length and width). The differences in the research samples can be observed quantitatively.